PENGARUH KREDIT BERMASALAH TERHADAP SISA HASIL USAHA DI KOPERASI SWAMITRA MITRA BANK BUKOPIN - deri firmansyah, deri firmansyah; Wiwi warsiati (JEBS (Journal of Economic and Business Student), 2022)
Abstrak Non-performing loans as an independent variable (Variable X), Remaining Operating Results as dependent variable (Variable Y), the research used in this study is a descriptive method with an associative approach, where this research provides benefits for descriptive purposes and helps in assessing conditions - existing conditions with predetermined criteria and also in the implementation of the evaluation. The results showed that in general the number of non-performing loans against SHU at the Swamitra Mitra Bank Bukopin Cooperative, non-performing loans from 2007 to 2011 tended to rise and fall. The development of SHU followed the development of non-performing loans up and down. The effect of bermaskah credit on SHU is only 18.49%, of which 81.51% is influenced by other factors, other than non-performing loans. Kata Kunci:keredit,SHU